α-Smooth Muscle Actin and ACTA2 Gene Expressions in Vasculopathies - Yuan,Shi-Min (2015)
ABSTRACT α-smooth muscle actin, encoded by ACTA2 gene, is an isoform of the vascular smooth muscle actins, typically expressed in the vascular smooth muscle cells contributing to vascular motility and contraction. ACTA2 gene mutations cause a diversity of diffuse vasculopathies such as thoracic aortic aneurysms and dissections as well as occlusive vascular diseases, including premature coronary artery disease and ischemic stroke. Dynamics of differentiation-specific α-smooth muscle actin in arterial smooth muscle cells and proliferation of the proteins have been well described. Although a variety of research works have been undertaken in terms of modifications of α-smooth muscle actin and mutations of ACTA2 gene and myosin, the underlying mechanisms towards the pathological processes by way of gene mutations are yet to be clarified. The purpose of the present article is to describe the phenotypes of α-smooth muscle actin and implications of ACTA2 mutations in vasculopathies in order to enhance the understanding of potential mechanisms of aortic and coronary disorders.